The ANALYSIS OF CAPITAL ASSET PRICING MODEL (CAPM) AND REWARD TO VARIABILITY RATIO (RVAR) AS A BASIS FOR STOCK INVESTMENT DECISION MAKING - Zainal Abidin; Dyah Ciptaning LSW; Halimatus Syadiah (Nusantara Journal Of Management Business (NUMABI), 2024)
Study This aim For analyze grouping efficient stock or worthy as alternative For compile A good portfolio with use Capital Asset Pricing Model ( CAPM) method . Then the suitability of these shares can be sorted based on the optimal level of return and risk level using the Reward To Variability Ratio (RVAR). The method used in this research is a descriptive method with a quantitative approach. The sample used is the share movement of all companies listed on the LQ45 index on the Indonesia Stock Exchange during 2020-2023 with a total of 5 companies.